Characterisation of the temperature and time dependent mechanical properties and solder - Tan, Kwang Hong. (2008)
Eutectic 63Sn-37Pb solder is commonly used as interconnects in SMT electronic packages. Characterisation of the temperature and time dependent properties of eutectic solder is necessary in understanding solder joint reliability. The effect of thermal cycling ageing on solder joint mechanical properties and residual fatigue strength requires research attention. This report documents the investigation conducted on the determination of the mechanical properties of bulk solder specimens, the microstructural and mechanical response of solder after subjecting reflowed solder joint to thermal cycling ageing from -40°C to 125°C.